The biological function of Serpinb9 and Serpinb9-based therapy - Huang, Haozhe; Mu, Yiqing; Li, Song (Frontiers in Immunology, 2024)
Recent breakthroughs in discovering novel immune signaling pathways have revolutionized different disease treatments. SERPINB9 (Sb9), also known as Proteinase Inhibitor 9 (PI-9), is a well-known endogenous inhibitor of Granzyme B (GzmB). GzmB is a potent cytotoxic molecule secreted by cytotoxic T lymphocytes and natural killer cells, which plays a crucial role in inducing apoptosis in target cells during immune responses. Sb9 acts as a protective mechanism against the potentially harmful effects of GzmB within the cells of the immune system itself. On the other hand, overexpression of Sb9 is an important mechanism of immune evasion in diseases like cancers and viral infections. The intricate functions of Sb9 in different cell types represent a fine-tuned regulatory mechanism for preventing immunopathology, protection against autoimmune diseases, and the regulation of cell death, all of which are essential for maintaining health and responding effectively to disease challenges. Dysregulation of the Sb9 will disrupt human normal physiological condition, potentially leading to a range of diseases, including cancers, inflammatory conditions, viral infections or other pathological disorders. Deepening our understanding of the role of Sb9 will aid in the discovery of innovative and effective treatments for various medical conditions. Therefore, the objective of this review is to consolidate current knowledge regarding the biological role of Sb9. It aims to offer insights into its discovery, structure, functions, distribution, its association with various diseases, and the potential of nanoparticle-based therapies targeting Sb9.